2009
DOI: 10.12693/aphyspola.115.181
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of Magnetic and Transport Properties οf UAuSb2Single Crystals

Abstract: The uranium-gold diantimonide UAuSb2 belongs to a numerous family of ternary compounds crystallizing in a tetragonal structure of the HfCuSi2-type (space group P 4/nmm). In this paper the results of magnetization, electrical resistivity and thermopower measured along the main crystallographic directions are reported. Two magnetic transitions, a ferromagnetic one at TC = 31 K and probably an antiferromagnetic one at TN = 43 K were found. The spontaneous magnetization at 1.9 K amounts about 0.8 µB for B c-axis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…The fundamental physical properties of the ternary uranium diantimonides with the chemical formula UT x Sb 2 (x is some deficit of T atoms being Co, Ni, Cu and Au) have already been studied using monocrystalline materials [1][2][3][4]. These studies revealed their very strong anisotropy and substantial deficiency in the transition metal site occupancy of Co, Ni and Cu, similar to those found previously for their rare earth counterparts, e.g.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…The fundamental physical properties of the ternary uranium diantimonides with the chemical formula UT x Sb 2 (x is some deficit of T atoms being Co, Ni, Cu and Au) have already been studied using monocrystalline materials [1][2][3][4]. These studies revealed their very strong anisotropy and substantial deficiency in the transition metal site occupancy of Co, Ni and Cu, similar to those found previously for their rare earth counterparts, e.g.…”
Section: Introductionsupporting
confidence: 61%
“…This probably concerns also UAuSb 2 , exhibiting in this series a full occupation of the Au layer, for which two magnetic transitions i.e. the ferromagnetic at T C = 31 K and antiferromagnetic at T N = 43 K, have been found [4]. Thus, the electronic band structure of this Au-based compound http has been calculated by the full potential linear muffin-tin orbital (LMTO) method [11].…”
Section: Introductionmentioning
confidence: 87%
“…Table 1 shows the results of the refinement, while the atomic coordinates and occupancy factors are provided in Table 2 . The refined lattice parameters and unit cell volume are a = 0.436320(6) nm, c = 0.978574(3) nm and V = 0.1862963(6) nm 3 , which are smaller than those reported for UAuSb 2 ( a = 0.4375(1) nm, c = 0.9831(2) nm) 19 . Upon refining the site occupancies keeping those of the U site fixed to one, the Sb sites are very close to being fully occupied, but the occupancy of the Au site is 0.792(2).…”
Section: Resultsmentioning
confidence: 55%
“…The partially occupied UAu 0.8 Sb 2 shares some similarities to both UAuSb 2 and USb 2 . UAuSb 2 likely undergoes two magnetic transitions, a ferromagnetic one at T C = 31 K and a possible antiferromagnetic transition at T N = 43 K 19 . Meanwhile USb 2 undergoes an antiferromagnetic transition at 203 K, with no other magnetic transitions at lower temperature 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion from the both series of the band structure calculations is that the direction [111] is the easy axis of magnetization and the magnetocrystalline anisotropy is strong, the anisotropy constants K, K 2 are of the order of magnitude 16, 5-6 MJ/m 3 . Magnetic measurements on UAuSb 2 [11] indicate that this conclusion can be valid.…”
Section: Discussionmentioning
confidence: 72%